2014
DOI: 10.1371/journal.pone.0103194
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of Tri- and Hexavalent Chromium Compounds In Vivo and Their Modes of Action on DNA Damage In Vitro

Abstract: Chromium occurs mostly in tri- and hexavalent states in the environment. Hexavalent chromium [Cr(VI)] compounds are extensively used in diverse industries, and trivalent chromium [Cr(III)] salts are used as micronutrients and dietary supplements. In the present work, we report that they both induce genetic mutations in yeast cells. They both also cause DNA damage in both yeast and Jurkat cells and the effect of Cr(III) is greater than that of Cr(VI). We further show that Cr(III) and Cr(VI) cause DNA damage thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(84 citation statements)
references
References 45 publications
2
73
0
1
Order By: Relevance
“…increased γ-H2AX, a sensitive indicator of DNA DSB, in Caco-2 cells (Thompson et al, 2012). Therefore, Cr(VI)-induced DNA damage may be responsible for cell cycle delay, as observed in MG-63 cells in the present study through the positive correlation between the increasing showed that Cr(VI) induced DNA DSB in normal human dermal fibroblasts (Ha, Ceryak, & Patierno, 2004), HeLa cells (Wakeman et al, 2004) and T-lymphocyte Jurkat cells (Fang et al, 2014), as well as Cr-DNA, DNA-DNA and DNA-protein crosslinks in normal human lung cells (LL 24 cell cline) (Fang et al, 2014;Xu, Bubley, Detrick, Blankenship, & Patierno, 1996). In studies by Ha et al (2004), Wakeman et al (2004) and Xu et al (1996) In previous studies using non-osteoblasts, treatments with K 2 Cr 2 O 7 for 24-30 hours induced chromosome breaks as well as aneuploidy after a short post-exposure time of 24-30 hours (Figgitt et al, 2010;Güerci, Seoane, & Dulout, 2000;Seoane, Güerci, & Dulout, 2002).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…increased γ-H2AX, a sensitive indicator of DNA DSB, in Caco-2 cells (Thompson et al, 2012). Therefore, Cr(VI)-induced DNA damage may be responsible for cell cycle delay, as observed in MG-63 cells in the present study through the positive correlation between the increasing showed that Cr(VI) induced DNA DSB in normal human dermal fibroblasts (Ha, Ceryak, & Patierno, 2004), HeLa cells (Wakeman et al, 2004) and T-lymphocyte Jurkat cells (Fang et al, 2014), as well as Cr-DNA, DNA-DNA and DNA-protein crosslinks in normal human lung cells (LL 24 cell cline) (Fang et al, 2014;Xu, Bubley, Detrick, Blankenship, & Patierno, 1996). In studies by Ha et al (2004), Wakeman et al (2004) and Xu et al (1996) In previous studies using non-osteoblasts, treatments with K 2 Cr 2 O 7 for 24-30 hours induced chromosome breaks as well as aneuploidy after a short post-exposure time of 24-30 hours (Figgitt et al, 2010;Güerci, Seoane, & Dulout, 2000;Seoane, Güerci, & Dulout, 2002).…”
Section: Discussionsupporting
confidence: 66%
“…Using the same cell line other authors found that Cr(VI) changed the expression of proteins involved in energy metabolism, stress signalling and proliferation (cytoskeletal proteins) (Raghunathan, Grant, & Ellis, ). Although genotoxic effects have been detected in several human cell types exposed to Cr(VI) (Fang et al, ; Novotnik, Ščančar, Milačič, Filipič, & Žegura, ; Thompson et al, ; Wise, Holmes, Liou, Adam, & Wise, ) it is pertinent the thorough investigation of such effects in human osteoblasts as they are also targets of Cr(VI). The aim of this work was to evaluate the effects of clinically relevant concentrations of Cr(VI) in human osteoblasts, by integrating genotoxicity results with possible changes in the cell cycle and cell viability, and assess the usefulness of these endpoints as reliable clinical biomarkers of Cr(VI)‐induced toxicity in bone tissues of patients using MoM prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…34 There is growing evidence that chromium (III) is genotoxic 35 , highlighting the importance of measuring total chromium. In our study, we could not measure the valence state of chromium.…”
Section: Discussionmentioning
confidence: 99%
“…Once inside the cells, CrVI is readily converted into CrIII by AOXs such as ascorbate, glutathione (GSH), and cysteine. CrIII was initially thought to be relatively non-toxic, however, it was found to be more damaging than CrVI in causing genotoxicity in cell free systems (Fang et al, 2014). CrIII interacts with DNA and induces DNA strand breaks, DNA-protein crosslinks and oxidative DNA base modifications (Nickens et al, 2010; Fang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%